OBTENCION DE PLANTAS A PARTIR DE EMBRIONES SOMATICOS DE QUERCUS SUBER L - Fernández Guijarro, B; CELESTINO, C; TORIBIO, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This paper gives a procedure to regenerate plants of cork oak through somatic embryogenesis. The somatic embryos were obtained in leaves from young seedlings and cotyledonary fragments from mature acorns of cork oak. The explants were cultured in three stage process in wich BA and NAA concentration were decreasing. Different methods were used to germinate the embryos. Dessication and culture in low salt concentration medium were chosen to give the best results
Keywords: adventive embryogenesis; Cork oak; culture media; plant regeneration; secondary embryogenesis